Investigating depression, anxiety, perceived stress and resilience in fathers faced with their spouse’s abortion in Iran: a longitudinal study - Seyede Zahra Jafari; Mahboubeh Hajifoghaha; Sara Azima; Parvin Ghaem Maghami; Zahra Yazdan Panahi (BMC Psychiatry)
Abstract Background Abortion is a stressful event that can often affect the mental health of both parents. It seems that resilient people can adapt to stressful situations. The mental health of fathers plays an important role in improving the mental health of the family, but few studies have been conducted in this regard. Therefore, this study aimed to investigate depression, anxiety, perceived stress and resilience of fathers faced with their spouse’s abortion. Methods This longitudinal study was conducted on 125 spouses of women hospitalized in the post-partum department of Shiraz hospitals in 2023. Data collection tools included questionnaires of demographic and fertility characteristics, hospital depression and anxiety (HADS), Cohen’s perceived stress, and Connor’s resilience. The data were analyzed through Spss24 software using Friedman’s tests and post hoc tests, Adjusted Bonferroni, Kruskal-Wallis and Mann-Whitney tests. Results The mean age of the fathers was 35.02 ± 6.22. The scores of the father’s anxiety, depression, and perceived stress from 24 h to 12 weeks after abortion were decreased significantly. However, their resilience score increased significantly. Also, there was a significant relationship between the fathers’ age, education, job, duration of marriage, type of abortion, number and history of abortion, unwanted pregnancy, number of children and economic status with the mean score of anxiety, depression, perceived stress, and resilience in fathers over time. Conclusion This research pointed out the effect of abortion on depression, anxiety, and perceived stress in fathers; also, resilience as a coping factor could affect these disorders and improve the fathers’ mental health. Therefore, screening and managing mental disorders in them are important to improve family health.